Short-term dynamics of leaf litter-derived soil organic carbon under different coffee and cocoa cropping systems - Erwin Prastowo; Laily Mukaromah (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2020)
Litter plays a crucial role in the formation of soil organic carbon (SOC), and potentially affects different pools in the context of soil carbon cycle. To improve knowledge and understanding with respect to the dynamics of carbon in coffee and cocoa cropping systems, there is a need to develop a mechanistic model to explain the formation of carbon especially in different background of soil, climate and agronomic management. Short-term observation was performed in different cropping systems, i.e. coffee (Coff) and cocoa (CoL) with lamtoro(Leucaena sp.) shade trees, and cocoa with oil palm (Elaeis guineensis) shade trees (CoP), and teak (Tectona grandis) conservation area, to investigate the quantitative amount of leaf litter-derived carbon. Additionally, to improve the understanding with respect to the formation of soil organic carbon, a simple model is developed by employing organic carbon storage coefficient (hi) as parameter to validate the observation data from Coff and CoL plots. Leaf litter is collected daily with concomitant microclimate records, i.e. air temperature, relative humidity, light intensity, and soil temperature. Composite soil and leaf samples are collected for organic carbon, soil moisture content, and leaf relative water content (RWC), for laboratory identification. Analysis of data suggests the presence of cropping system effect, i.e. shading condition and agronomical practices such as pruning, to microclimate variations except for soil temperature. Furthermore, cropping systems do not significantly influence soil moisture content, amount of organic carbon, and RWC. With higher model efficiency (EF), the simulated model fits better for CoL, EF 0.95, than Coff, EF 0.58. Model simulation, with both hi values are 0.017 and 0.014 in Coff and CoL, reveals a possibly cropping system specific curve pattern. A faster SOC formation in Coff plot has suggested a crucial role the amount of leaf litter to support with continuous carbon supply. The simulation implies the presence of soil related-maximum point limiting carbon storage capacity